2019
DOI: 10.3168/jds.2018-15274
|View full text |Cite
|
Sign up to set email alerts
|

Rumen microbial responses to supplemental nitrate. I. Yeast growth and protozoal chemotaxis in vitro as affected by nitrate and nitrite concentrations

Abstract: Nitrates have been fed to ruminants, including dairy cows, as an electron sink to mitigate CH 4 emissions. In the NO 3 − reduction process, NO 2 − can accumulate, which could directly inhibit methanogens and some bacteria. However, little information is available on eukaryotic microbes in the rumen. Protozoa were hypothesized to enhance nitrate reductase but also have more circling swimming behavior, and the yeast Saccharomyces cerevisiae was hypothesized to lessen NO 2 − accumulation. In the first experiment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Preliminary searches of the genome of Entodinium caudatum returned annotated nitrate reductase (personal communication, Tansol Park, The Ohio State University, Columbus), which should be expected based on previous studies comparing protozoal enriched samples versus bacterial samples (Yang et al, 2016). Increasing concentration of NO 2 − profoundly inhibited motility of entodiniomorphids (of which E. caudatum is a predominant member) and entodiniomorphid chemotaxis in our companion study (Roman-Garcia et al, 2019), so NO 2 − reduction by protozoa awaits further inquiry. There was no difference in generation time between NO 3 − , LYC, or their interaction.…”
Section: Nitrogen Outflow To Effluentmentioning
confidence: 58%
See 1 more Smart Citation
“…Preliminary searches of the genome of Entodinium caudatum returned annotated nitrate reductase (personal communication, Tansol Park, The Ohio State University, Columbus), which should be expected based on previous studies comparing protozoal enriched samples versus bacterial samples (Yang et al, 2016). Increasing concentration of NO 2 − profoundly inhibited motility of entodiniomorphids (of which E. caudatum is a predominant member) and entodiniomorphid chemotaxis in our companion study (Roman-Garcia et al, 2019), so NO 2 − reduction by protozoa awaits further inquiry. There was no difference in generation time between NO 3 − , LYC, or their interaction.…”
Section: Nitrogen Outflow To Effluentmentioning
confidence: 58%
“…In addition to consuming O 2 , LYC could also stabilize pH by stimulating lactilytic strains of Selenomonas ruminantium (Pinloche et al, 2013), which also are important in NO 3 − and NO 2 − reduction (Yang et al, 2016). In our companion study (Roman-Garcia et al, 2019), we questioned if LYC would reduce NO 2 − in microaerophilic conditions and thereby help prevent its accumulation after NO 3 − is fed, but the hypotheses were not supported, perhaps because of a lack of microbial adaptation to NO 3 − . Our objectives were to evaluate the effect of dietary NO 3 − and its potential interaction with LYC on fermentation characteristics, microbial protein synthesis, and prokaryotic community composition in continuous cultures that are adapted to NO 3 − for 7 d. We hypothesized that NO 3 − would suppress methanogenesis and shift bacterial populations toward those reducing NO 3 − and NO 2 − , and LYC would suppress methanogenesis additively with feeding NO 3 − while decreasing NO 2 − accumulation to result in increased NDF digestibility and efficiency of bacterial growth.…”
Section: Introductionmentioning
confidence: 89%
“…Isotrichids are highly chemotactic toward glucose and xylose (Diaz et al, 2014) and almost certainly other sugars. Peptides can be both chemoattractive and chemorepellent to isotrichids (Diaz et al, 2014;Roman-Garcia et al, 2019). Hence, uncontrolled glycogenesis in vitro (Jouany and Ushida, 1999;Hall, 2011) probably is lessened in vivo because of much less abrupt increase in sugar availability.…”
Section: Acquisition Of Substratementioning
confidence: 99%
“…The reduction of NO2- disappearance rate after adding NO2- to the SOL fraction of FAU and DEF rumen digesta could be due to a toxic effect of NO2- on rumen micro‐organisms, although final NO2- concentration in the buffer added to the rumen digesta was 0.5 mM which is below the 2 mM NO2- , value reported to inhibit microbial growth (Iwamoto, Asanuma, & Hino, 2002). More recently, Roman‐Garcia et al (2019) found that in vitro motility and chemotaxis within protozoa were affected differently by NO2- but not NO3- for isotrichids versus entodiniomorphids. However, the addition of NO2- increased NH 3 accumulation rate in both fractions of rumen digesta, suggesting no adverse effects of NO2- on rumen micro‐organisms in this current experiment.…”
Section: Discussionmentioning
confidence: 99%